Dual GSK3β/SIRT1 modulators for Alzheimer’s: mechanisms, drug discovery and future perspectives - Kareem, Afeez I.; Kapp, Erika; Joubert, Jacques; Zou, Xiaoqin (Frontiers in Pharmacology, 2025)
Alzheimer’s disease (AD) remains without effective disease-modifying therapies, in part due to the limited efficacy of single-target approaches. Dual modulation of glycogen synthase kinase-3β (GSK3β), a key driver of tau hyperphosphorylation and amyloid-β (Aβ) production, and sirtuin-1 (SIRT1), a neuroprotective NAD+-dependent deacetylase, has emerged as a promising therapeutic strategy. This review explores the mechanistic rationale for concurrently inhibiting GSK3β and activating SIRT1 to disrupt AD’s pathological cascade while enhancing endogenous neuroprotective pathways. Natural compounds such as resveratrol, berberine, pterostilbene, and quercetin exhibit this dual activity and provide scaffolds for rational drug design. However, challenges related to target selectivity, blood-brain barrier penetration, and clinical translation persist. Advances in multi-target drug discovery, including pharmacophore hybridization, structure-based modelling, cheminformatics, nanoformulation and delivery strategies offer new avenues to overcome these hurdles. A dual GSK3β/SIRT1-targeting strategy exemplifies a systems-level approach to restoring neurophysiological balance and holds potential to achieve more effective, disease-modifying outcomes in AD.